A Review of Technology Acceptance and Adoption Models in Consumer Study - Naseri, Roszi Naszariah Nasni; Azis, Siti Noraziana; Abas, Norlela (FIRM Journal of Management Studies, 2023)
User acceptance of technology has been a key area of study for numerous studies. Businesses could determine the path for future development by understanding user acceptability. A variety of frameworks and models have been created to describe how users embrace new technologies, and these models add variables that may have an impact on user acceptance. An overview of theories and concepts related to user acceptability of technology are given in this study. The growth of each theory, as well as its most important applications, expansion and limitations are summarised in this paper. In addition it provides a summary of the technological acceptance and adoption model in consumer study. Through this review, future researchers will be better able to conceptualise, identify, and appreciate the underlying technological models and theories that may influence future application of technology adoption.